The effect of improved safety on fuel economy of European cars - Zachariadis, Theodoros (My University, 2008)
This paper considers whether increased safety in modern cars has been an obstacle for automakers to fulfil voluntary CO2 emission reduction commitment in Europe. It examines two basic questions: how much safety affects vehicle mass in modern cars, and whether a safer car consumes more fuel than its less safe counterparts. Results from safety tests performed by EuroNCAP on 192 car models were examined looking at vehicle mass, engine size, fuel consumption and CO2 emissions. The results seem to confirm findings from the US and international studies: the enhanced safety of modern cars has a very small effect on vehicle mass and does not significantly affect fuel consumption.
Keywords: Fuel consumption; Europe; Transportation--Safety measures; Automobiles--Crashworthiness